2017
DOI: 10.14746/sr.2017.1.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Application of Attachement Theory to Equine-Facilitated Therapy

Abstract: Over the past two decades there has been a growing body of evidence, clinical and anecdotal, that equine-facilitated therapy (EFT) is a powerful tool for social workers and mental health clinicians. Recent research studies have begun to identify, name, and explain the mechanisms of EFT as a treatment tool for individual clients. However, EFT lacks a unified theoretical foundation; many studies lack an explicit theory altogether. Strong empirical support begins with a strong theoretical foundation, the research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, in their article on equine-assisted group therapy, they suggest that animals in therapy may be able to offer the experience of such an attachment, offering a relationship in which children feel safe, can experiment with extending themselves, and return for comfort and reassurance when their capacity is overwhelmed. This is supported by Vincent and Fargas [27], who argue that relationships between horses and humans can be studied in the context of attachment theory, and by Bachi [8], who suggests that Bowlby's attachment theory can be used to explain the theory and practice of equine-assisted interventions. In this article, we investigate the potential development of attachment relationships between young people and horses according to the four principal features of attachment by Bowlby [13,15].…”
Section: Horses In the Creation Of Therapeutic Space: The Applicationmentioning
confidence: 92%
See 1 more Smart Citation
“…However, in their article on equine-assisted group therapy, they suggest that animals in therapy may be able to offer the experience of such an attachment, offering a relationship in which children feel safe, can experiment with extending themselves, and return for comfort and reassurance when their capacity is overwhelmed. This is supported by Vincent and Fargas [27], who argue that relationships between horses and humans can be studied in the context of attachment theory, and by Bachi [8], who suggests that Bowlby's attachment theory can be used to explain the theory and practice of equine-assisted interventions. In this article, we investigate the potential development of attachment relationships between young people and horses according to the four principal features of attachment by Bowlby [13,15].…”
Section: Horses In the Creation Of Therapeutic Space: The Applicationmentioning
confidence: 92%
“…Previous research has shown certain features of a typical attachment bond to be fulfilled in human–dog companionship [ 26 ], but there is a considerable lack of research on the attachment in human–horse relationships. Following the call by Bachi [ 8 ] and Vincent and Farkas [ 27 ], who argue that human–horse dyads should also be reviewed in the context of attachment theory, the aim of this qualitative case study is to examine if even a short-term exposure to horses may bring about elements of emerging attachment for adolescents. Specifically, we will look at the four elements of attachment bond named as principal features by Bowlby: (1) proximity maintenance, (2) safe haven, (3) secure base, and (4) separation distress [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interacting with horses can help clients overcome various emotional challenges such as anxiety, depression, and trauma. Through the presence of horses as creatures sensitive to nonverbal expression and responsive to emotional changes, clients can establish a deep connection with these animals [11]. Activities such as feeding, grooming, or direct interaction with horses can create a supportive environment forexploring and understanding the feelings and thought patterns underly-ing psychological issues [12].…”
Section: Equine-assisted Psychotherapy (Eap)mentioning
confidence: 99%
“…However, there are distinct differences in how humans interact with companion animals versus other animals, and there are gaps in understanding if different approaches to the intervention are equally effective. Not all youth who may benefit from health services actually access them, so using animals may encourage engagement [43], particularly if research approaches preserve the integrity of the therapeutic environment. Primary reasons for choosing horse-assisted interventions by families and caregivers are for enhancing this emotional regulation and improving life functioning, particularly when secondary conditions exist [44].…”
Section: Theoretical Implicationsmentioning
confidence: 99%